Scandium(III) triflate immobilised in ionic liquids: a novel and recyclable catalytic system for Friedel-Crafts alkylation of aromatic compounds with alkenes - Song, CE; Shim, WH; Roh, EJ; Choi, JH (ROYAL SOC CHEMISTRY, 2000)
Scandium(iii) triflate catalysed Friedel-Crafts alkylation of aromatic compounds with alkenes proceeded readily in the hydrophobic ionic liquid solvents based on 1,3-dialkylimidazolium salts with easy catalyst/solvent recycling, whereas these reactions did not occur in common organic solvents, water or hydrophilic ionic liquids at all.
Keywords: ORGANIC-SYNTHESIS